Quantifying spatial variability of soil and leaf nitrogen, phosphorus, and potassium of basal stem rot infected oil palms using geospatial information system - Tajudin, Nur Shuhada; Musa, Mohamed Hanafi; Abu Seman, Idris; Che Amri, Che Nurul Aini (Malaysian Palm Oil Board, 2020)
Basal stem rot disease (BSR) is known to be responsible for yield losses in oil palm plantations in Southeast Asia. A balance nutrient in soil and leaf is known to improve the plant health and disease resistance. In order to observe how nitrogen (N), potassium (P) and phosphorus (K) content in soil and leaf affect the BSR occurrence, a field study was conducted in infected blocks of oil palms at two different ages. Nutrients variability (N, P and K) were obtained, analysed and mapped using classical statistics and geospatial method. Correlated to BSR disease, total N and available P in soil were found to be high in both blocks. However, exchangeable K exhibited low level. Total N and available P in soil of Blocks 1 and 2, and N and P in leaves of Block 1 showed a significant association with the disease (p<0.01). The generated variability map and significant correlations revealed that imbalanced nutrient content occurred in the study area. This would be one of the causes that lead to the disease outbreak.